An evaluation of the usability of sludge from the mechanical-biological sewage tratment plant of the town of Zielona Góra for sewage farming = Ocena przydatności osadów ściekowych z mechaniczno-biologicznej oczyszczalni miasta Zielona Góra do rolniczego wykorzystania - Drab, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper contains an evaluation of the possibilities of using sludge from the town of Zielona Góra in agriculture. The sludge under research demonstrated positive fertilizing properties. It has been found that because of increasing sludge doses the crops of plants grown have increased.
Keywords: ścieki; oczyszczalnia mechaniczno-biologiczna; rolnicze wykorzystanie ścieków; sludge; sewage farming